TRENDS IN MUZAKKI AND BUSINESS ZAKAT COLLECTION IN BRUNEI DARUSSALAM - binti Nor Irdi, Amal Hadzimatul Nadzirah; bin Muda, Zulkifly (Islamic Economics Program, Faculty of Islamic Economics and Business, 2024)
One of the branches of zakat in Islam is Business Zakat. In Brunei Darussalam, the department responsible for zakat matters is the Department of Zakat, Waqaf, and Baitulmal, the Ministry of Religious Affairs (JUZWAB). Business zakat payers and collections are generally ranked third after zakat on savings and zakat on gold. The number of business zakat contributors are relatively small compared to the total number of registered companies in Brunei Darussalam. This will be elaborated and analyzed, particularly regarding the trends in muzakki (zakat payers) and business zakat collected from 2019 to 2023. The objectives of this study are to provide the number of muzakki and the amount of business zakat collected in Brunei Darussalam and analyzes the trends in the number of muzakki and the amount of business zakat collected in Brunei Darussalam. This study is a qualitative research and data used in this study is obtained from JUZWAB. The findings of this study indicate an increase in the number of business zakat contributors from the 50s to the 70s between 2019 and 2023 and the annual amount collected from business zakat does not follow a consistent pattern and may fluctuate year by year. This paper recommends that JUZWAB identify the factors causing some Muslim traders not to pay business zakat and provide appropriate recommendations to address these issues.